2019
DOI: 10.1017/s1368980019002064
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of an FFQ for South American children and adolescents from the SAYCARE study

Abstract: Objective:The purpose of this study was to analyse the reliability and validity of a semi-quantitative FFQ to assess food group consumption in South American children and adolescents.Design:The SAYCARE (South American Youth/Child cARdiovascular and Environmental) study is an observational, multicentre, feasibility study performed in a sample of 3- to 18-year-old children and adolescents attending private and public schools from six South American countries. Participants answered the FFQ twice with a two-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
2
15
2
5
Order By: Relevance
“…The Pearson's correlation coefficients of reproducibility for most of the nutrients and foods groups were slightly higher than those obtained in a validation study assessing diet in a five-month period with children and adolescents in Australia where the average of correlation coefficients for reproducibility was 0.32 [28]. Other studies in adolescents have shown higher correlation coefficients in reproducibility than those shown in this study [29][30][31][32]. One reason for the higher correlations observed in those studies could be the much shorter interval used between the two FFQ administrations, which ranged from two weeks to one month.…”
Section: Discussioncontrasting
confidence: 82%
“…The Pearson's correlation coefficients of reproducibility for most of the nutrients and foods groups were slightly higher than those obtained in a validation study assessing diet in a five-month period with children and adolescents in Australia where the average of correlation coefficients for reproducibility was 0.32 [28]. Other studies in adolescents have shown higher correlation coefficients in reproducibility than those shown in this study [29][30][31][32]. One reason for the higher correlations observed in those studies could be the much shorter interval used between the two FFQ administrations, which ranged from two weeks to one month.…”
Section: Discussioncontrasting
confidence: 82%
“…This study aimed to validate the FFQ and the combination of the frequency of intake from the FFQ with the 24 h-DR (mean of 3 days), both designed for the SAYCARE Study, for children’s fruit and vegetable intake. The reproducibility of the SAYCARE FFQ for this food group was previously tested by comparing it against the 24 h-DR [21], with fair agreement in children. Consequently, now we are conducting the validity the SAYCARE FFQ with a superior and objective method, the plasma vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…More details on the development and validity of the semi-quantitative FFQ designed for the SAYCARE Study [20] and its validity were described elsewhere [21]. The SAYCARE FFQ refers to usual consumption from the last three months.…”
Section: Methodsmentioning
confidence: 99%
“…Despite a general decent relative reliability of food consumption estimates from FFQs, the absolute reliability is a challenge [36,37]. Overestimates in consumption frequency are common, especially for foods perceived as healthy or socially desirable [38], and this bias may increase with the length of the food list [1].…”
Section: Impacts On Contaminant Intake Assessmentmentioning
confidence: 99%